Comparison of 1,3-β-d-glucan with galactomannan in serum and bronchoalveolar fluid for the detection of Aspergillus species in immunosuppressed mechanical ventilated critically ill patients - Lahmer, Tobias; Neuenhahn, Michael; Held, Jürgen; Rasch, Sebastian; Schmid, Roland M.; Huber, Wolfgang (Journal of Critical Care, 2016)
Invasive pulmonary aspergillosis (IPA) is an important cause of morbidity/mortality in immunocompromised critically ill patients. New diagnostic strategies for early detection of IPA include the noninvasive biomarkers 1,3-?-d-glucan (BDG), serum, and bronchoalveolar (BAL) fluid galactomannan (GM). The aim of this study was to compare these markers for early detection of IPA in immunosuppressed critically ill patients.Between December 2014 and December 2015, 49 immunosuppressed patients with respiratory failure were treated at our intensive care unit (ICU). We compared the BDG Fungitell assay with GM Platelia assay in serum and BAL for early detection of IPA. All tests were performed initially after admission at the ICU.In our study with 49 patients, 13 (26%) had probable IPA. These patients had a higher Acute Physiology And Chronic Health Evaluation II score (28 vs 23, P<.001), Sequential Organ Failure Assessment score (16 vs 14, P<.001), more neutropenia (77% vs 30%, P<.001), worse Horowitz Index (99 vs 73 P<.020), a longer ICU stay (26 vs 17 days, P<.044), and a higher mortality rate (77% vs 58%, P<.001) as compared with patients without probable IPA. The used biomarker BDG presented in patients with probable IPA showed significantly higher levels as compared with patients without probable IPA (375 [103-1000 pg/mL; P<.001] vs 64 [30-105 pg/mL; P < .001]). Comparison of BDG with GM showed that positive serum GM could be detected in only 4 (30%), whereas positive BAL GM could be detected in 12 (92%; mean optical density index, 3.7) of 13 probable IPA cases. These results can be expressed as an overall sensitivity of 88% and a specificity of 82% for probable IPA using the BDG Fungitell assay, a sensitivity of 35% and a specificity of 70% using the serum GM Platelia assay, and a sensitivity of 70% and a specificity of 94% using the BAL GM Platelia assay. The negative predictive values of the used tests were 94% for the BDG Fungitell assay, 94% for the serum GM Platelia assay, and 90% for the BAL GM Platelia assay.1,3-?-d-Glucan may be a useful marker for patients under surveillance at risk for IPA. In critically ill patients with immunosuppression, early diagnosis of IPA may be improved by BDG as compared with serum GM. However, diagnostic performance and accuracy increase when BDG is run in parallel with GM from BAL; moreover, the association of the 2 parameters has also the advantage of detecting early and reliable IPA.
EVALuna2:7720